Mengatasi Kesulitan Siswa Kelas 1 Sekolah Dasar dalam Menulis Permulaan - Pebrika, Agnes; Senditia, Ai Astrid; Salsabila, Nabila; Nurkhoeriah, Siti (MASALIQ, 2023)
This article discusses efforts to overcome the difficulties faced by first-grade elementary school students in their initial writing. Writing is an essential foundational skill in the learning process, but first-grade students often encounter challenges in developing their writing abilities. Some common obstacles they face include difficulties in understanding letter concepts and using appropriate vocabulary. This research aims to find effective methods and strategies to assist first-grade students in overcoming difficulties in their initial writing. This was carried out at SD Negeri 182/1 Muara Bulian Protected Forest. The research methodology involves classroom observations, interviews with teachers, and qualitative analysis of student writing outcomes. The research results demonstrate that an approach focused on playful learning activities, the use of images or visual aids, and involving social interactions can enhance students' interest and motivation to write. Furthermore, providing positive and constructive feedback and introducing diverse reading materials also help improve students' writing skills. By implementing suitable approaches and strategies, it is expected that first-grade elementary school students can overcome their difficulties in initial writing and develop their writing abilities more effectively.